Analysis of CO2 Absorption Capacity and Carbon Storage in Mangroves in Kendari Bay Mangrove Tracking Area - Florensia, Keryn; Sudia, La Baco; Bana, Sahindomi; Gandri, La; Indriyani, Lies; Siwi, La Ode; Erif, La Ode Muhammad; Fathnur, Fathnur (Proceeding International Conference on Religion, Science and Education, 2025)
Carbon dioxide (CO2) levels in nature are increasing along with the development of human civilization. On the other hand, mangrove forests can absorb and store carbon in large quantities, and for a long time, so they can play a role in mitigating climate change. This study aimed to determine the potential for CO2 uptake and carbon storage in the Kendari Bay Mangrove Tracking area, Lahundape Village, West Kendari District, Kendari City. This research was conducted in June 2023 in the Kendari Bay Mangrove Tracking area, Lahundape Village, West Kendari District, Kendari City. The sampling in this study used a purposive sampling method; the determination of sampling was selected systematically with a sampling intensity of 4%. The placement of measuring plots is based on the zoning of 8 (eight) plots of mangrove forests, where each plot is 20 m x 20 m (400 m2). Variables in this study are the diameter at breast height of adults to determine biomass and carbon above ground without cutting trees (nondestructive). Biomass was determined using the Allometric equation. The carbon was determined by ½ of the biomass. The results showed that the potential for CO2 uptake and carbon storage in the Kendari Bay Mangrove Tracking area, Lahundape Village, West Kendari Subdistrict, Kendari City, has an average CO2 uptake of 90.99 tons ha-1 and carbon storage of 24.79 tons ha-1. The amount of carbon value is influenced by environmental conditions, type of wood mass, mangrove stem diameter, and the number of species contained in a plot.